Evaluation of fermented rice bran to replace soybean meal in the diet of Clarias sp. fingerling: Evaluasi fermentasi dedak padi untuk menggantikan tepung kedelai pada pakan benih ikan lele Clarias sp - Putra, Achmad Noerkhaerin; Syamsunarno, Mas Bayu; Rohayati, Dede; Sarah, Yuhana Marta; Matien, Ghulam Abdul (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
Rice bran is being fermented using Aspergillus niger in order to increase its usage as a raw material for the catfish diet. This research aims to evaluate the potentials of rice bran fermented with A. niger to replace soybean meal in catfish Clarias sp diet. There were two research stages, first the fermentation test of A. niger on rice bran that used a completely randomized factorial design consisting of 2 factors, namely the dose of A. niger (0, 0.5, 1, 1.5, and 2 g/100 g) and incubation time (0. 24 and 48 hours). Secondly, the substitution test of soybean meal with fermented rice bran on five different of substitution levels (0, 15, 20, 35, and 40%) in the catfish diet. The results showed that the fermentation of A. niger of 2 % with an incubation period of 24 hours in rice bran resulted in the smallest crude fiber and fraction content, and increased protein and amino acid including serine, threonine, alanine, methionine, isoleucine, and lysine. The specific growth rate in the substitution treatment of 0-20% was significantly (P<0.05) higher than that of 35-40%. There was also no difference (P>0.05) in the growth performance of catfish in the 0 to 20% substitution treatment. Also, replacing soybean meal with fermented rice bran up to 20% did not have a negative effect on the growth performance of catfish. It was concluded that fermented rice bran could be used as raw material for catfish.